UPAYA PENINGKATAN PARTISIPASI MASYARAKAT KELURAHAN SUMBER REJO KECAMATAN KEMILING BANDAR LAMPUNG DALAM PELAKSANAAN SISTIM KEAMANAN LINGKUNGAN - Fajryan, Tahta Kharisma; Kahono, Gunawan Budi (SOCIOLOGIE, 2013)
The security system is the implementation of the security environment spontaneous organized society in implementing environmental safeguards. This system will ensure an optimum if the community actively participated. The importance of public participation in the implementation of environmental security system is based on the phenomenon of crime in an increasingly complex society. The results of this research indicate that public participation in the implementation of the security system environment on Sumber Rejo Subdistric Kemiling District of Bandar Lampung included in the high category (participate). It is based on the data as many as 38 (42.22%) of respondents who participated in the implementation of security environment system.Keywords: Public participation, security system environment